Metal Oxide Porous Coatings for Implantant Materials - Skatkov, L.; Lyashok, L.; Gomozov, V.; Tokareva, I.; Kolupaev, I.; Bayrachniy, B. (Journal of Coating Science and Technology, 2015)
The paper presents the results of survey, dedicated to synthesis of metal oxide coatings on porous materials applied for implant surgery (stainless steel 12X18H9T, titanium alloy and high-purity niobium VT5). This article examines kinetic features of electrochemical formation of anodic oxide coatings on steel, niobium and titanium. It is shown that for steel anodic treatment method does not provide a reliable surface passivation (no current decay, the surface indicates the transition to the passive state). Analysis of polarization dependences obtained on niobium and titanium in electrolytes with an activator (F-), indicates surface passivation (current slump), and at potentials above 2 on the surface of a transition curves in transpassive state (as evidenced by the current increase). Consequently, it can be concluded that presence of F- results surface activation of titanium and niobium electrode (F- oxide reacts to form water-soluble complexes) that promotes nucleation and formation of pores of the porous structure of the oxide coating. SEM results verify the presence of self-organized porous oxide film synthesized on titanium and niobium in solutions containing F-.